PT Madina Solusi Indonesia Fiber to the Home (FTTH) Perancangan menggunakan GPON Teknologi (Studi Kasus : PT. Madina Solusi Indonesia): Penelitian - Miftah Farid; Singgih Prastyo Nugroho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research focuses on designing a Fiber To The Home (FTTH) network in Perumnas Condongcatur, Yogyakarta, with Gigabit Capable Passive Optical Network (GPON) technology. in the area. The project is driven by the increasing need for reliable internet  services  according to  the eligibility  standards  of the Indonesia Digital Network (IDN) program. This research includes results according to technical, economic, and social aspects related to FTTH design. The use of Google Earth and Opticsystem software resulted in attenuation  of less than -28dBm for attenuation feasibility measurements. The results of this gpon-based infrastructure design are expected to provide a solution for PT Madina Solusi Indonesia in providing internet services that support digital transformation in the region.